2011
DOI: 10.1007/s00508-010-1523-x
|View full text |Cite
|
Sign up to set email alerts
|

The advantages of humeral anteromedial plate osteosynthesis in the middle third shaft fractures

Abstract: An anteromedial plating of humeral shaft fractures through anterolateral approach was determinated to be a simple, safe, effective and also fast surgical treatment and we highly recommend it as operative technique for treating humeral shaft fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 12 publications
3
15
0
Order By: Relevance
“…Incidence of radial nerve palsy in posterior plating has been reported to be 11.14%. [6] In our study we did not have any radial nerve palsy.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Incidence of radial nerve palsy in posterior plating has been reported to be 11.14%. [6] In our study we did not have any radial nerve palsy.…”
Section: Discussionmentioning
confidence: 54%
“…Plate fixation results in high union rates but requires extensive dissection and soft tissue stripping [3]- [5]. The most commonly used approaches for treating these fractures are posterior and anterolateral [6]- [10]. The incidence of radial nerve palsy through posterior approach is 11% and anterolateral plating is 5.4% [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies by Kirin et al and Senthil et al in which plate was placed on medial surface did not show wrist drop. 10,11 Majority of the patients had clinical (87%) and radiological union (74%) during second follow up at three months. The range of motion at first, second and third follow ups showed gradual increase in mean flexion, abduction, external rotation and internal rotation.…”
Section: Discussionmentioning
confidence: 99%
“…The studies in which plate was positioned on medial surface, by Kirin et al, Senthil et al, Dayez et al concluded that, there was no requirement for blood transfusion for any of the patients, radial nerve palsy was not observed in any of the case immediately after surgery. [10][11][12] Evidence of union was seen between six to twelve weeks. Our experience was same regarding the need of blood transfusion, time period of healing, simplicity of procedure, safety and time duration of surgery.…”
Section: Discussionmentioning
confidence: 99%